Artificial Intelligence in Madrasah Libraries of Bangladesh: Status, Readiness, and Adopiton Challenges - Md. Mostafizur Rahman; Badhan Hubert Corraya (IQRO: Journal of Islamic Education, 2026)
This study assesses the current state, readiness, and perceptions regarding artificial intelligence (AI) integration in madrasah libraries across Bangladesh, identifying key challenges and opportunities for modernization. A quantitative cross-sectional survey was employed with 300 respondents: students, teachers, librarians, and principals from both Alia and Qawmi madrasahs, analyzed using descriptive statistics, chi-square tests, Kruskal-Wallis H tests, and reliability analysis (Cronbach's α=.801). Traditional print resources dominate library usage, yet 47% of respondents rely on smartphones for internet access, reflecting adaptive hybrid connectivity. Infrastructure limitations (38.7%) and lack of trained staff (31.7%) are the primary barriers to AI adoption, far outweighing ideological resistance (16%). Notably, 68% express willingness to adopt AI-based library services, with unanimous agreement (M=4.00, SD=0.00) that AI aligns with Islamic values. A significant association exists between digital resource availability and AI adoption readiness (χ²=20.369, p=.002). This systematic assessment of AI readiness in Bangladeshi madrasah libraries challenges prevailing assumptions regarding an inherent conflict between religious values and technology, demonstrating significant cultural receptivity despite existing infrastructural limitations. The findings hold direct policy relevance for Bangladesh's Vision 2041 digital transformation agenda. Policymakers and madrasah administrators are advised to prioritize investments in equitable infrastructure and staff training, rather than focusing on fostering cultural acceptance, as the evidence suggests that practical capacity, rather than religious or ideological resistance, constitutes the primary barrier to AI adoption in madrasah libraries.